PERANCANGAN SISTEM KONTROL ROBOT BIPED DELAPAN SENDI DENGAN SENSOR GS-12 SEBAGAI SENSOR KESETIMBANGAN DAN SENSOR DMS-80 SEBAGAI PENDETEKSI HALANGAN - Vitro Luthfiakbar Rais; Nazori AZ (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Biped robots are two-legged robots that can run like humans. This robot has a foot structure like humans and has joints that represent the legs, knees and hips. In biped robots, the balance still runs when it stays inside walking. In this final project a biped robot has been made that can move forward in a balanced manner and can avoid obstacles. Making this Biped Robot to improve the compatibility of robots that move forward and avoid obstacles without falling. The working principle used is, the robot compilation is activated, the robot is in a position ready the GS-12 sensor will be active and the DMS-80 sensor will discuss the obstacles ahead, if there is no obstacle the robot will move forward and the compilation of sensors then the robot will avoid to the right if the sensor reading value is DMS-80 = 146 or left if the sensor reading value of DMS-80 = 71, and the GS-12 sensor will read so that the robot does not fall in every movement. From the overall test it can be concluded, the eight-joint biped robot with the GS-12 sensor as an equilibrium sensor and DMS-80 sensor as a barrier detector. In this test the robot can be run according to the command given. In testing the robot, it can be seen the number of robot falls, namely, the total robots fell 39 times out of 5 tests, 3 types of movements and 28 steps of movement.